Numerical and theoretical analysis of a straight bevel gear made from orthotropic materials - Al-Qrimli, Haidar; Abdelrhman, A.; Khiled, K. (2017)
© 2017 Jordan Journal of Mechanical and Industrial Engineering. The purpose of the present study is to present a clear fundamental thought for designing and investigating straight bevel gear made of composite material. Application of composites in modern engineering includes gear-drive components, such as robotic arms, and this is especially evident when metallic gears are incapable of coping with the vigorous requirements of the machines. The presentwork demonstrates an actual form of the straight bevel gear that is made out into a set of equation rearranged and derived from the classical theory of gearing. The gear is then modeled using CAD commercial software in order to generate the whole gear in three dimension coordinates. This analytical calculation was constructed to allow us to calculate the straight bevel gear profile points, which are crucial for modeling and fabricating the composite gear model and to numerically analyze this model using finite element method. The results were extensively compared. This comparison attempted to study the composite bevel gear teeth problem. The focus in this work is on how much the divergence in behavior between orthotropic material and isotropic material such as steel can be reduced. The results prove the capability or potential for composite materials to be used as component materials in power transmission gearing in robotic arms applications.